Pengaruh Persyaratan Usia Terhadap Peluang Kerja Bagi Tenaga Kerja Di Indonesia - Shelomita Putri Amelia; Aurelya Putri Alzahrah; Dewi Safira (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The Age limit requirements on job vacancies are currently being criticized by the public through social media. Age restrictions are a form of age discrimination. Companies/employers often set an age limit for workers ranging from 18-25 years old. This age requirement is considered to make it difficult for prospective workers to find work, especially for contract workers and women. This study describes the limitation of working age as a form of discrimination and the policies governing age requirements in Indonesia. The research method used in this research is normative legal research using a statute approach, comparative approach, and conceptual approach. The results of this study show that in Indonesia there are no regulations or policies that regulate and provide legal protection regarding age discrimination of workers and it is important for the government and companies to consider more inclusive policies related to age restrictions in recruitment. In addition, there needs to be an effort to provide training and employment opportunities for workers who are above the age limit so that they can still be productive.